Age-related changes in cognitive biases during adolescence. (July 2019) - Slavny, Rachel J.M.; Sebastian, Catherine L.; Pote, Helen
Abstract: Introduction: Age has been found to moderate the relation between cognitive biases and psychopathology, yet little is known about normative age-related change in these biases during adolescence. Adolescence might be a key developmental period for changes in negatively biased information-processing, and understanding the trajectories of these processes in a typically developing population is a pre-requisite for further comprehending their association with psychopathology. Methods: This study explores the effect of age on seven cognitive biases in a diverse community sample from the United Kingdom ( N  = 540) aged 10–17 years (309 were female) using self-report measures. Results: Age demonstrated a positive linear association with three biases: threat interpretation, negative attributions and overgeneralizing scores. Conclusions: Important changes take place during adolescence that may increase young people's negative cognitive biases. Empirical data on normative age-related changes in cognitive biases should be integrated into theoretical models of biased information-processing and psychopathology. Highlights: We investigated the effect of age on seven cognitive biases in adolescents. Age showed a positive linear association with three biases. Changes during adolescence may increase young people's negative cognitive biases.